Safety Baby Shower Intervention Improves Safe Sleep Knowledge and Self-Efficacy among Expectant Teens - Mary E. Aitken MD, MPH; Leanne Whiteside-Mansell PhD; Samantha H. Mullins MPH; Shasha Bai PhD; Beverly K. Miller MEd (SAGE Publishing, 2023)
Introduction Young, minority women are less likely to follow recommendations to prevent infant sleep-related deaths putting their children at risk. This study extended the past pre/post study designs to an RCT design and included both parent report and objective observation of the sleep environment. Objective This study focused on this population in a quantitative, randomized controlled trial using a low-cost, brief educational intervention, a Safety Baby Shower (SBS). Methods Pregnant teens aged 13-19 (N = 147) were recruited as a dyad with a senior female caregiver and randomized to intervention or control groups. Results Comparing self-report, safe sleep knowledge, attitudes, beliefs, and intent (KABI) to act scores across the two groups found intervention dyads to have more positive views on all four constructs than controls. Specifically, intervention dyad young mothers were significantly more likely to have positive beliefs about safe sleep and were more likely to report intent to practice infant safe sleep than control young mothers. Intervention dyad young mothers also had higher self-efficacy related to infant safety and more positive attitudes about safe sleep practices than control young mothers. Observations at a home visit conducted after delivery found no differences in the safe sleep practices by intervention status. Participant report of behaviors at the home visit also showed no differences in the use of safe position between the intervention and control groups. Conclusion It appears that even when young mothers gain knowledge and self-efficacy, they have difficulty implementing this knowledge. In practice, this suggests that exploring barriers prenatally with this population and offering suggestions to overcome them may be indicated.